2002
DOI: 10.1055/s-2002-33245
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Unexplained Acute and Acute Recurrent Pancreatitis Using Endoscopic Retrograde Cholangiopancreatography, Sphincter of Oddi Manometry and Endoscopic Ultrasound

Abstract: An etiology was identified in the majority of patients with unexplained pancreatitis. SOD represented the most common finding. Moderate to severe chronic pancreatitis was found in over one-fifth of these patients. Bile analysis, SOM, and EUS are useful tools in the evaluation of unexplained acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
1
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(82 citation statements)
references
References 19 publications
3
70
1
8
Order By: Relevance
“…A basal pressure and phasic contractions of Oddi's sphincter could be obtained with OSM. OSM during ERCP is a useful tool in the evaluation of patients with unexplained pancreaticobiliary pain or recurrent idiopathic pancreatitis [5][6][7] . However, it might provoke serious pancreatitis [8,9] .…”
Section: Discussionmentioning
confidence: 99%
“…A basal pressure and phasic contractions of Oddi's sphincter could be obtained with OSM. OSM during ERCP is a useful tool in the evaluation of patients with unexplained pancreaticobiliary pain or recurrent idiopathic pancreatitis [5][6][7] . However, it might provoke serious pancreatitis [8,9] .…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective and competitive blinded study in patients with CBD obstruction EUS gave 100% accuracy for the diagnosis of choledocholithiasis; it was also significantly more sensitive than transabdominal ultrasonography or CT [10] . In patients with unexplained ARP the use of EUS with high resolution increases the chances of detecting microlithiasis ( Figure 3), a frequent cause of pancreatitis [2,11,12] . A large study by Frossard et al evaluated 168 patients referred with diagnosis of idiopathic pancreatitis.…”
Section: Microlithiasismentioning
confidence: 99%
“…Cystic lesions that cause duct compression or involvement of the main pancreatic duct tend to cause pancreatitis. EUS identified all tumoral causes in a recent series of 90 patients with undetermined causes of acute or recurrent pancreatitis [2] . Cystic neoplasms of the pancreas are traditionally organized according to the type of lining epithelium since this feature dominates the risk of malignancy and management.…”
Section: Pancreatic Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Coyle et al determined the diagnostic utility of ERCP with sphincter of Oddi manometry, bile analysis and EUS in patients with acute and acute recurrent idiopathic pancreatitis [6]. Authors concluded that EUS was useful in detecting biliary disease and anatomic anomalities and valuable in detecting early changes of chronic pancreatitis.…”
Section: Studies On Yield Of Eusmentioning
confidence: 99%